CHANGES IN KNOWLEDGE OF EARLY MARRIAGE THROUGH PEER INFORMATION - Wahyuningsih, Sri; Musviro; Nurul Hayati; Aprilika Merza Yulis (Universitas STRADA Indonesia, 2024)
Background : The Human Development Index (HDI) consists of three components, namely the education index, health index, and purchasing power. Method : The type of research is quantitative using paired T-test and with pretest and post-test methods in one group (one-group pre-test and post-test design). Result : Shows that the paired T-test results get p-value = 0.001 which means less than 0.05. Conclusion : The contribution/peer information that influences in the direction of good knowledge in early marriage, both directly related to the decision to marry at an early age and with behaviors that encourage marriage.